Development of Fuzzy Inference System for Automatic Tea Making - Ahamed, Nizam Uddin; Zahari, Taha; Ismail, Mohd Khairuddin; Rabbi, M. F.; Sikandar, Tasriva; Palaniappan, Rajkumar; Ali, Md. Asraf; Rahman, S. A. M. Matiur; Sundaraj, Kenneth (IEEE, 2017)
In this paper, a fuzzy inference system has been developed for automatic tea making process. The system takes five inputs and gives two output which determines the grade of black tea and milk tea. Specifically, the proposed system considers five important characteristics of hot tea beverage such as water temperature, sugar, milk, brewing time and tea leaves quantity for grading the standard of the drink according to the consumer’s requirement. Both black tea and milk tea can be rated with a grade based on the human expert judgment which is according to the taste and aroma of the tea. This automatic tea making system can let the users choose their preferred type of tea without figuring out the complicated process to making a cup of hot tea beverage.